Medicinal Plants Used in Treatment of Noninfectious Skin Diseases: A Systematic Review - S Kianbakht (Institue of Medicinal Plants, ACECR, 2012)
The use of medicinal plants and plant active constituents in the treatment of skin diseases is very common. Here, primarily the clinical trials concerning the use of medicinal plants and plant active constituents in the treatment of noninfectious skin diseases published in English from the beginning of the year 2000 to the end of the year 2012 in the databases PubMed and Scopus are discussed. Many studies have been conducted in this field so far and further studies to determine the efficacy and safety of these drugs in the treatment of skin diseases seem necessary.